Increased pupillary constriction velocity in benign essential blepharospasm associated with photophobia - Byun, Yong-Soo (PLoS One, 2019)
We evaluated whether the pupillary light reflex is altered in benign essential blepharospasm patients. Twenty-three patients with benign essential blepharospasm, 47 with reflex blepharospasm, and 29 dry eye disease controls were included. Pupillary light reflex-related parameters were measured under mesopic (10 lux) and photopic illuminance (200 lux) using an infrared pupillometer. Additionally, we assessed photophobia grade, eyelid function, and dry eye disease-related parameters. There were no differences in age, sex predominance, or dry eye disease-related parameters among the three groups, or in photophobia grade and eyelid function between benign essential blepharospasm and reflex groups. Constriction velocity and maximum constriction velocity in the mesopic condition were significantly greater in the benign essential blepharospasm group (3.26 ± 0.56 and 5.27 ± 0.90 mm/s) than in reflex (2.86 ± 0.62 and 4.59 ± 1.00 mm/s) or dry eye disease groups (2.96 ± 0.46 and 4.72 ± 0.67 mm/s). Constriction velocity and maximum constriction velocity in the mesopic condition positively correlated with photophobia grade (r = 0.525 and 0.617, P = 0.025 and 0.006) in the benign essential blepharospasm group. Pupillary light reflex may be related to the pathophysiology of benign essential blepharospasm with photophobia. Further studies are required to reveal connections among pupillary light reflex, photophobia, and focal dystonia in benign essential blepharospasm patients with photophobia.